The dramaturgy of a puerperium: a videodance based on the Klauss Vianna Technique (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article presents the creative process and the construction of the dramaturgy of the videodance parTidabased on the Klauss Vianna Technique (TKV) of dance and somatic education. The videodance was performed by both authors, one who dances in the process of mothering and the other who guides her in the creation process. The creative process at TKV considers procedurality as a principle, improvisation as a technique and lability as a characteristic of choreography. Dramaturgy emerges from the mobility and combination of these factors and other scenic elements, incorporating the unique experience of each body that dances. The videodance reveals the slow departure of a body that was born from another, and the learning of both bodies to live apart. The creative research in TKV is shown here as a political action and reveals it as a possible methodology for a maternal artivism.
Keywords: artvideodance; Klauss Vianna technique; creative process; dramaturgy; maternal art